International perceptions and African agency: Uganda and its donors 1986-2010 - Fisher, J (2011)
This thesis investigates the place of African states in the international system and seeks to understand what space exists for aid-dependent governments to exercise agency in relations with donors. In exploring these issues I focus on the case of Uganda’s NRM regime which has enjoyed very substantial international support despite its increasingly authoritarian nature, destabilising regional policy and questionable human rights record. The two central questions posed are therefore: ‘why has Uganda benefited from such uncritical international support and what role has the NRM regime itself played in bringing about this situation?’ The thesis also compares Uganda’s experience to those of Ethiopia, Kenya and Rwanda to demonstrate the broader relevance of these questions. I argue that donors have taken a lenient approach to Uganda because they perceive it as valuable as an economic success story, an ally in the ‘War on Terror’ and a guarantor of regional stability. The study stresses, however, that these perceptions are just that: perceptions. They do not necessarily reflect reality nor are they formed without input from Africa, as some inadvertently suggest. Indeed, the principal contention of this thesis is that these three donor perceptions of Uganda have been actively constructed, moulded, managed and bolstered by Kampala itself in an effort to shore-up international support. Using a variety of ‘image management’ strategies the regime has succeeded in convincing its donors to see it as a valuable ally worth supporting. The same is true of the Rwandan and Ethiopian governments, I suggest, but not of the Kenyan. In doing so, the thesis contends, Kampala has carved out a subtle but substantial degree of agency in relations with donors and this raises important questions for scholars and policy-makers.